Les journalistes face aux réseaux sociaux? Une nouvelle relation entre médias et politiques - Jean-Hugues Roy (Communiquer)
Valérie Jeanne-Perrier looks at how social media has transformed relationships between journalists, politicians and the public. All three groups have become “holograph”, says the author, meaning that social media enables them to be active and present everywhere and all the time. The initial promise that social media would renew and modernize those relationships has however not been accomplished.